2011
DOI: 10.1126/science.1195691
|View full text |Cite
|
Sign up to set email alerts
|

Translation-Independent Localization of mRNA in E. coli

Abstract: Understanding the organization of a bacterial cell requires the elucidation of the mechanisms by which proteins localize to particular subcellular sites. Thus far, such mechanisms have been suggested to rely on embedded features of the localized proteins. Here, we report that certain messenger RNAs (mRNAs) in Escherichia coli are targeted to the future destination of their encoded proteins, cytoplasm, poles, or inner membrane in a translation-independent manner. Cis-acting sequences within the transmembrane-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
266
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(292 citation statements)
references
References 29 publications
19
266
3
4
Order By: Relevance
“…In line with that, several bacterial mRNAs were shown to localize near the chromosomal loci from which they are expressed. 24 In a recent publication in Science, 25 we showed that, contrary to the general thinking in the field, bacterial mRNAs are capable of migrating to particular positions in the cell, where their future protein products are required. 25 Our results were based on imaging of live and fixed cells and were validated by a biochemical approach.…”
Section: Localization Of Bacterial Proteins Via Mrna Targetingmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with that, several bacterial mRNAs were shown to localize near the chromosomal loci from which they are expressed. 24 In a recent publication in Science, 25 we showed that, contrary to the general thinking in the field, bacterial mRNAs are capable of migrating to particular positions in the cell, where their future protein products are required. 25 Our results were based on imaging of live and fixed cells and were validated by a biochemical approach.…”
Section: Localization Of Bacterial Proteins Via Mrna Targetingmentioning
confidence: 99%
“…24 In a recent publication in Science, 25 we showed that, contrary to the general thinking in the field, bacterial mRNAs are capable of migrating to particular positions in the cell, where their future protein products are required. 25 Our results were based on imaging of live and fixed cells and were validated by a biochemical approach. Thus far, we followed the localization of bacterial mRNAs that code for proteins that localize to the cytoplasm, the inner membrane, or the poles (Fig.…”
Section: Localization Of Bacterial Proteins Via Mrna Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…Site-specific and hence asymmetric mRNA localization was first observed for b-actin mRNA in ascidian embryos [48]. Recently targeting of mRNA was also shown in Escherichia coli, challenging the view of coupled transcription and translation in prokaryotes [49]. In mammals, mRNA localization has been observed and extensively researched in nerve cells with their often very long extensions [50].…”
Section: Cellular Infrastructure: Localized Protein Expression and DImentioning
confidence: 99%
“…Also localization signals can be found in certain bacterial proteins, similarly to their eukaryotic analogs (Russell and Keiler, 2007). Correspondingly, there is evidence of subcellular localization of certain mRNA transcripts correlating with the localization of their protein products (Nevo-Dinur et al, 2011). Yet another mechanism for protein positioning was brought up by the discovery of cytoskeletal proteins in bacteria (Vats et al, 2009).…”
Section: Introductionmentioning
confidence: 96%